Promoting Agrifood Sector Transformation in Bangladesh : Policy and Investment Priorities - Ahmed, Mansur (Washington, DC: World Bank, 2021)
Agriculture plays a central role in Bangladesh’s economy, especially in rural areas, and further progress in agriculture will remain important as Bangladesh’s economy continues to evolve. Bangladesh has made significant agricultural policy reforms since the 1980s, which has largely contributed to achieving self-sufficiency in rice production. However, these policies are now creating headwinds, constraining the emergence of a more diversified production system. With rapid urbanization and income growth, dietary patterns are changing in Bangladesh and new market opportunities are emerging for diverse, safe, and nutritious foods. Thus, additional productive diversification in agriculture and modernization along the agri-food value chain are needed in order to allow the sector to seize the emerging domestic market opportunities. Promoting greater diversification and modernization of the agri-food sector in Bangladesh will require repurposing the country’s agricultural support along with increasing private investment, both along the agri-food value chain and in support services to that chain. The agri-food ecosystem analysis in the report has identified critical constraints to the diversification and modernization of the agri-food sector. The major productivity constraints include land fragmentation and informality in the land rental markets; limited access to quality seeds for nonpaddy crops; limited knowledge of and adoption of good agricultural practices, reflected in unbalanced use and overuse of inputs; and limited use of farmer aggregation models, which constrains the delivery of extension services, access to financing, and linking with markets. Other key constraints, which are preventing off-farm value addition and commercialization in the sector, include the limited number of formal off-takers; inadequate and costly marketing infrastructure and logistic services; inadequate upholding of appropriate food safety practices and product quality standards; and a poorly designed export subsidy policy. These constraints are exacerbated by other cross-sectoral issues, such as access to finance, and the overall challenges of the investment climate and competitiveness.